2015
DOI: 10.1007/s12603-015-0640-7
|View full text |Cite
|
Sign up to set email alerts
|

Accelerometer assessment of physical activity and its association with physical function in older adults residing at assisted care facilities

Abstract: Despite engaging in physical activity levels far below current recommendations (150 min/week of MVPA or > 7000 steps/day), the most active older adults in this study exhibited clinically significant differences in physical function relative to their less active peers. While the direction of causality cannot be determined from this cross-sectional study, these findings suggest a strong association between PAL and physical function among older adults residing in an assisted care facility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 30 publications
4
29
2
1
Order By: Relevance
“…Furthermore, sedentary behaviour ascertained by questionnaire analysis was associated with lower grip strength in a study by Hamer and Stamatakis [38]. Other studies have also reported positive associations between objective measures of PA and grip strength [12, 17]. It is possible that HSSe participants may not have been taking part in activities that benefit upper extremity strength.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, sedentary behaviour ascertained by questionnaire analysis was associated with lower grip strength in a study by Hamer and Stamatakis [38]. Other studies have also reported positive associations between objective measures of PA and grip strength [12, 17]. It is possible that HSSe participants may not have been taking part in activities that benefit upper extremity strength.…”
Section: Discussionmentioning
confidence: 99%
“…Associations between PA and better function have also been observed in older adults in assisted care facilities. For example, better accelerometer-based PA was associated with a better short physical performance battery (SPPB) score, grip strength and faster walk speed in older adults aged over 65 [17]. A recent meta-analysis of 25 studies by Steffl et al concluded that PA, measured by self-report as well as with accelerometers, was associated with reduced odds of acquiring lower muscle mass or ‘sarcopenia’, in later life [18].…”
Section: Introductionmentioning
confidence: 99%
“…En primera instancia, deben generarse protocolos de uso de acelerómetros en ámbitos clínicos y de actividad física, segundo se deben realizar más estudios en relación a la validez y la confiabilidad del uso de los acelerómetros en diversos tipo de población, tercero la calibración de los equipos debe ser esencial para garantizar resultados objetivos en las investigaciones que se realicen con estos equipos. Adicionalmente, se deben seguir haciendo estudios con el fin de hacer esta tecnología asequible para investigaciones en actividad física y salud y rehabilitación con el fin de determinar riesgos cardiometabólico para la salud basados en niveles de actividad física y identificar parámetros de normalidad de marcha en pacientes con enfermedades osteomusculares y neuromusculares con el fin de dirigir actividades de intervención objetivas y ajustadas a metas impuestas por estos sistemas de información (5,8,58,59).…”
Section: Discussionunclassified
“…Only 4 studies [11][12][13][14] met all quality criteria. Twelve studies [15][16][17][18][19][20][21][22][23][24][25][26] scored between 8 and 10 and four [27][28][29][30] studies scored between 4 and 7. All studies complied with the inclusion/exclusion criteria, although the majority of studies did not provide a summary of the differences between those who participated and those who did not.…”
Section: Quality Of Studies Includedmentioning
confidence: 99%
“…The studies included in this review were cross sectional studies (n=17), 11,[15][16][17][18][19][20][21][22][23][25][26][27][28][29][30] cohort studies (n=2) 12,13 and prospective study (n=1). 24 They were conducted in Europe (United Kingdom, n=3; Portugal, n=2; German, Island, Norway, and Deutschland, all n=1), Australia (n=1), North America (USA n=5, Canada, n=2), Brazil (n=1), and Japan (n=1) ( Table 2).…”
Section: Study and Participants' Characteristicsmentioning
confidence: 99%